The ecoterrorism as the threat for the policy of balanced development. Ideological and practical aspects - Ciszek, Mariusz (Studia Ecologiae et Bioethicae, 2010)
The balanced development is the conception friendly attitude to the matter of protecting the human’s social and natural environment. More ecological organizations accept this idea, which they try to introduce in life. However, we can meet with the activity of those ecological organizations which have a radical character and in fact, they have much less common with the conception of balanced development and they are even opposite. The balanced development does not aim to set back the social and economical development of human civilization, but it tries to reconcile with the requirements of the protection of the natural environment (to balance). The ideology of some ecological radicals’ formations, their methods of working ( the practical aspect) show, however, that in fact such seen the comprehended development of human civilizations is with their point of sight too moderated and not to accept. The author in this article introduced the basic arguments that supported such opinions. He characterized also the individual extreme ecological organizations and he tried to establish on the basic literature of this object the border which permits to distinguish from these radical organizations those which we can recognize as an ecoterrorist.